2023
DOI: 10.1136/bmjgh-2022-011535
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to medicines and beyond: the national volume-based procurement policy in China

Abstract: .Since 2019, the Chinese central government has taken significant steps to centralize national purchasing power and has implemented a pooled procurement system. In this paper, we provide an in-depth analysis of China's National Volume-Based Procurement (NVBP) policy, which represents a unique approach to pooled procurement within the pharmaceutical sector. The primary objectives of the NVBP are to reduce drug prices, enhance access to affordable medications, and improve the overall functioning of the pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…However, some patients and doctors still had doubts about the safety and efficacy of the bid-winning drugs. It is necessary to explore more systematic approaches to boosting public confidence in bid-winning generic drugs and enhance physicians’ acceptability of them ( Zhu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients and doctors still had doubts about the safety and efficacy of the bid-winning drugs. It is necessary to explore more systematic approaches to boosting public confidence in bid-winning generic drugs and enhance physicians’ acceptability of them ( Zhu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study reported a higher price cut, suggesting that the concentration of national demand significantly strengthened our negotiating power. The centralised negotiation approach, combined with larger purchase quantities, allowed us to secure substantial price discounts 13 14…”
Section: Feasibility Of Pooled Procurement For Insulinmentioning
confidence: 99%
“…As the world’s second-largest pharmaceutical market, China’s previous rounds of pooled procurement for chemical drugs achieved more significant price cuts, improving bargaining power through pooling purchasing power across the nation 13. The NVBP received an unprecedentedly high political commitment 13 14. As described previously,13 14 under the direct supervision of the State Council, the Working Group—consisting of the National Healthcare Security Administration (NHSA), National Medical Products Administration (NMPA) and National Health Commission —is responsible for overseeing the regulation, evaluating and organising the procurement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations